Designing a Model of Organizational Authenticity, Its Antecedents and Consequences at Kerman University of Medical Sciences - Emamipour, Afsaneh; Kamali, Mohammad Jalal; Anjom Shoae, Zahra; Salajqeh, Sanjar (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: The present study was conducted with the aim of developing a model of organizational authenticity and identifying its antecedents and consequences at Kerman University of Medical Sciences. Methods and Materials: This study was applied-developmental in terms of purpose and qualitative in terms of research approach. Data were collected through a review of the relevant literature, upstream policy documents, and semi-structured interviews with 15 experts and managers from Kerman University of Medical Sciences. Participants were selected using purposive sampling, and interviews continued until theoretical saturation was achieved. Data were analyzed using thematic analysis with the assistance of MAXQDA 2018 software. Findings: The results of the data analysis led to the identification of a set of antecedents and consequences of organizational authenticity. The antecedents of organizational authenticity included authentic leadership, value-based organizational culture, organizational justice and trust, psychological safety, employees’ individual authenticity, and participation and empowerment. Furthermore, the most significant consequences of organizational authenticity included affective commitment, reduced turnover intention and absenteeism, public trust and organizational reputation, organizational citizenship behavior, intrinsic motivation, employee well-being, and creativity and innovation. The findings indicated that organizational authenticity is a multidimensional and dynamic phenomenon that emerges from the interaction of individual, managerial, and cultural factors and generates extensive outcomes for employees, organizations, and stakeholders. Conclusion: The findings suggest that organizational authenticity in medical universities is not merely an identity-related characteristic; rather, it represents a strategic mechanism for strengthening trust, enhancing organizational cohesion, and improving performance. The proposed model can assist managers and policymakers within the healthcare system in designing management interventions grounded in authentic organizational values and in promoting organizational effectiveness.